2004
DOI: 10.1242/jcs.01076
|View full text |Cite
|
Sign up to set email alerts
|

CRM1-dependent, but not ARE-mediated, nuclear export ofIFN-α1mRNA

Abstract: While the bulk of cellular mRNA is known to be exported by the TAP pathway, export of specific subsets of cellular mRNAs may rely on chromosome region maintenance 1 (CRM1). One line of evidence supporting this hypothesis comes from the study of mRNAs of certain early response genes (ERGs) containing the adenylate uridylate-rich element (ARE) in their 3′ untranslated regions (3′ UTRs). It was reported that HuR-mediated nuclear export of these mRNAs was CRM1-dependent under certain stress conditions. To further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 79 publications
2
45
0
Order By: Relevance
“…For example, the specific CRM1 inhibitor leptomycin B inhibits expression of cyclooxygenase-2 (95) and was shown to cause nuclear retention of c-fos mRNA, whereas general mRNA export appeared not to be affected (66). Furthermore, it was shown that CRM1 mediates the nuclear export of the transcript encoding interferon-␣1 (96). Notably, the truncation of the 3Ј-UTR that contains ARE sequences does not negatively affect the CRM1-dependent nuclear export of the interferon-␣1 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the specific CRM1 inhibitor leptomycin B inhibits expression of cyclooxygenase-2 (95) and was shown to cause nuclear retention of c-fos mRNA, whereas general mRNA export appeared not to be affected (66). Furthermore, it was shown that CRM1 mediates the nuclear export of the transcript encoding interferon-␣1 (96). Notably, the truncation of the 3Ј-UTR that contains ARE sequences does not negatively affect the CRM1-dependent nuclear export of the interferon-␣1 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…We further tested the correlation between mRNA export and antigen presentation by inserting the SL8 epitope in the IFN-α1 mRNA, which is exported through the CRM1 but does not bind the Rev protein (20). In this situation, Rev instead blocks IFN-α1 mRNA export by interfering with the CRM1, resulting in increased SL8 peptide production (Fig.…”
Section: Ribosomal Scanning Of Nonspliced Mrnas Gives Rise To Productmentioning
confidence: 99%
“…Generally, the nuclear export of bulk poly(A) 1 mRNA is mediated in metazoans by the transport receptor NXF1/Tap, together with its small cofactor Nxt1/p15 (reviewed in detail in [30,[53][54][55]). However, it has also been reported that, for example, c-fos mRNA, or the message encoding interferon-a1, is translocated from the nucleus to the cytoplasm by a completely unrelated transport pathway [34,56]. This pathway is characterized by the export receptor : 70 mM) for 3 h. After 1 h, the respective cultures were activated with PMA/ ionomycin as before.…”
mentioning
confidence: 99%